Open versus arthroscopic surgery for diffuse tenosynovial giant-cell tumours of the knee: a systematic review - Quaresma, Maria Beatriz (EFORT Open Rev, 2020)
Diffuse-type tenosynovial giant-cell tumours of the knee (D-TGCT) have a very high complication rate. The recurrence rate for D-TGCT is mainly dependent on an initially successful resection of the lesion. The standard of care for this disease involves early surgery with synovectomy. Available surgical techniques may include an arthroscopic or open surgery; however, there is a lack of consensus on which technique should be used, and when. Arthroscopic excision is effective in minimizing morbidity and surgery-related complications, while an open surgical technique provides a more successful resection with a lower incidence of local recurrence. We could not conclude with confidence which of the surgical techniques is better at stopping a progression towards osteoarthritis and the need for a total knee arthroplasty. Cite this article: EFORT Open Rev 2020;5:339-346. DOI: 10.1302/2058-5241.5.200005